Lack of evidence of porcine reproductive and respiratory syndrome virus (PRRSV) infection in domestic swine in Brazil - Ciacci-Zanella Janice Reis; Trombetta Cristiano; Vargas Ildara; Costa Denise Euclydes Mariano da (Ciência Rural, 2004)
This report describes the first prevalence of antibodies and experimental inoculation of suspected samples of porcine reproductive and respiratory syndrome virus (PRRSV) from ELISA positive pigs from swine herds in Brazil. Based on the hypothesis that this agent is present in swine herds worldwide, the objective of this work was to establish a diagnostic methodology and to investigate the occurrence of PRRSV in Brazilian swine herds. Fifty-four swine herds, the total number which imported genetic material (live pigs or swine semen) from countries where PRRS was endemic from 1990 to December 2000, from eight Brazilian States all included in this study. The sampling used was such as to detect a prevalence of infection of 5%, with a confidence level of 95%. A total of 3785 serum samples were tested for PRRSV antibodies by ELISA. Following the ELISA test, which was performed with two different commercial kits, all serum positive pigs were retested, examined and additional materials were collected. Viral isolation in permissive tissue culture cells and swine bioassays were performed. Additionally, reverse transcriptase polymerase chain reaction (RT-PCR) and nested RT-PCR were also performed. We could not demonstrate the presence of PRRSV or RNA of PRRSV by viral isolation or RT-PCR (or nested RT-PCR), respectively in all of the analyzed samples. Furthermore, the pigs inoculated with PRRSV suspicion samples did not seroconvert nor produce characteristic PRRS lesions in the swine bioassay. Thus, our results indicate no evidence of PRRSV in the samples analyzed from swine herds in this study.